SHM_415478_HST_3D Polygonal Stone Axe - Hagaeus, Thomas; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a polygonal stone axe from the Swedish Early Neolithic, collected in Sweden and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=411

Link to Sök I Samlingarna

https://samlingar.shm.se/object/405A7E45-4CB4-4B26-96DB-EB05F12DDC15
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; Museum Object; 3D Model; Swedish Early Neolithic; Dynamic Collections; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi